2012
DOI: 10.1074/jbc.m112.377176
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Pannexin 1 Attenuates Melanoma Progression by Reversion to a Melanocytic Phenotype

Abstract: Background: Panx1 is a channel-forming glycoprotein that regulates epidermal differentiation and proliferation. Results: Depletion of Panx1 in melanomas causes cell re-differentiation into a melanocytic-like phenotype and reduced tumorigenesis. Conclusion: Panx1 is up-regulated during melanoma progression promoting tumor growth and metastasis. Significance: This is the first report of Panx1 as a proto-oncogene establishing it as a potential target for melanoma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 44 publications
5
107
0
Order By: Relevance
“…The chick CAM avian embryo model has been widely used as a model for tumorigenesis in vivo, including the assessment of melanoma tumor growth and metastasis (26,31). We found that control melanomas produced relatively large tumors, not unlike tumors produced by Cx26-expressing melanomas.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The chick CAM avian embryo model has been widely used as a model for tumorigenesis in vivo, including the assessment of melanoma tumor growth and metastasis (26,31). We found that control melanomas produced relatively large tumors, not unlike tumors produced by Cx26-expressing melanomas.…”
Section: Discussionmentioning
confidence: 75%
“…In Vivo Chick Chorioallantoic Membrane (CAM) Assay-Primary tumor properties of BL6 cells in the chicken embryo was assessed as previously described (31). Briefly, fertilized chicken eggs (McKinley Hatchery, St. Mary's, Canada) were incubated in an automated rotary incubator (GQF Manufacturing Company) under 40% humidity at 37°C for 3 days, rotating once every hour.…”
Section: Methodsmentioning
confidence: 99%
“…In astrocytes, Connexin-43 is required for cell migration under pro-inflammatory conditions and it interacts with many cytoskeletal proteins, such as β-actin and glial fibrillary acidic protein [40,41]. Conversely, pannexins regulate motility of different cell types, such as neutrophils or leucocytes, tumor cells, venous fibroblasts, and neurons, among others [42][43][44]. Given these observations, we evaluated whether these hemichannels participate in Thy-1-induced migration of astrocytes by mediating ATP release and P2X7R activation.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Furthermore, Panx-1-depleted B16 melanoma cells exhibit reduced cell migration and growth, resembling normal melanocytes. Knockdown of Panx-1 in mice also has the effect of reducing tumor size in vivo [8]. Moreover, Panx-1 is highly expressed in human platelets, and Panx-1 channels can promote the aggregation of platelets, which is a risk factor of cancer metastasis, by enhancing Ca 2+ influx and ATP release [9].…”
mentioning
confidence: 99%
“…These data supported that Panx-1 has a tumorsuppressor property, while some other studies indicated that Panx-1 promotes the development of cancer. Penuela et al [8] found that Panx-1 is upregulated in B16 melanoma cells rather than in normal melanocytes. Furthermore, Panx-1-depleted B16 melanoma cells exhibit reduced cell migration and growth, resembling normal melanocytes.…”
mentioning
confidence: 99%